Hubungan Karakteristik Dengan Kesesuaian Bidang Kerja Lulusan Pendidikan DIII Kebidanan Di Jawa Barat - Sefrina Werni; Rosita Rosita; Nita Prihartini (Buletin Penelitian Sistem Kesehatan, 2020)
Midwifery education graduates ideally work as midwives. This study explored the relationship between characteristics and suitability the field of work graduates of DIII midwifery study program in 2019. This study applied a cross-sectional design with a quantitative approach. The population was graduates in 4 DIII midwifery study programs in West Java and the sample whose access the google form as many as 442 respondents. Google forms distributed by email, Facebook, and WhatsApp group graduates within one month. The dependent variable was the suitability the field of work graduate. In contrast, the independent variables were characteristics of graduate (the status of the study program, age, marital status, year of graduation, the value of IPK, and additional education after graduation). Analysis of data used chi-square. The results showed 10.2% of midwifery study program graduates worked not as midwives, 37.8% of them said that salary was the reason they did outside the midwife profession and another 15.6% expressed no interest as midwives. The results of the bivariate analysis showed that marital status and IPK at graduation had a significant relationship with the suitability of the graduate work field (p <0.005). The commitment of graduates as midwives is the main focus to enhance midwifery professionalism. The existence of graduates whose work outside the midwife profession along with their reasons provided information on the need for strengthening midwife salary standards based on labour regulations. Abstrak Lulusan pendidikan kebidanan idealnya bekerja sebagai bidan. Penelitian ini dilakukan pada tahun 2019 untuk menilai hubungan antara karakteristik dengan kesesuaian bidang kerja lulusan prodi DIII kebidanan. Penelitian menggunakan desain penelitian potong lintang dengan pendekatan kuantitatif. Populasi adalah lulusan di 4 prodi DIII kebidanan di Jawa Barat dan sampel adalah yang mengakses google form. Total sampel sebanyak sebanyak 442 responden. Google form yang disebarkan melalui email, facebook, dan whatsapp group lulusan dalam jangka waktu 1 bulan. Sebagai variabel terikat adalah kesesuaian bidang kerja lulusan, variabel bebas adalah karakteristik lulusan (status program studi, umur, status pernikahan, tahun lulus, nilai IPK, dan pendidikan tambahan setelah lulus). Data dianalisis menggunakan chi-square. Hasil penelitian menunjukkan 10,2% lulusan prodi DIII kebidanan bekerja bukan sebagai bidan, 37,8% diantaranya menyampaikan bahwa gaji merupakan alasan mereka bekerja di luar profesi bidan dan 15,6% lainnya menyatakan tidak berminat sebagai bidan. Hasil analisis bivariat memperlihatkan status pernikahan dan IPK saat lulus memiliki hubungan yang bermakna dengan kesesuaian bidang kerja lulusan (p<0,005). Komitmen lulusan sebagai bidan merupakan fokus utama untuk meningkatkan profesionalisme bidan. Keberadaan lulusan yang bekerja di luar profesi bidan beserta alasannya memberikan informasi perlunya penetapan standar gaji bidan dengan berpedoman pada aturan ketenagakerjaan.